Preparation of polymeric and ceramic porous capsules by a novel electrohydrodynamic process. - Nangrejo, M; Ahmad, Z; Stride, E; Edirisinghe, M; Colombo, P (2008)
The preparation of capsules for medical and industrial use can be achieved via several conventional routes, yielding either hard or soft receptacles, depending on the type and the content of the material to be encapsulated. Together with tablets, capsules are amongst the most commonly used means of administering medication and this makes progress in capsule preparation technology a key area of drug delivery research. Here we uncover new technology for the preparation of capsules with porous chambers. The novelty is signified in the use of an electrohydrodynamic process engineering route and its potential is elucidated using a polymeric material; polymethylsilsesquioxane, which can be converted into an identical ceramic form by means of simple pyrolysis. Thus, both polymeric and ceramic capsules have been prepared. The effects of process control parameters such as the applied voltage and flow rate, on the characteristics of the capsules prepared are discussed.